A long-term, high-efficiency, antibacterial and fully degradable medical zinc alloy / polylactic acid composite material and its preparation method

The zinc alloy/polylactic acid composite prepared by 3D printing technology has solved the problem of excessive corrosion and insufficient antibacterial strength in bone healing treatment through surface modification and the addition of MXene, thus achieving the effect of long-term efficient antibacterial and mechanical properties improvement.

CN116531575BActive Publication Date: 2025-04-22NANJING INST OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310479834.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-28
Publication Date
2025-04-22
Estimated Expiration
2043-04-28

AI Technical Summary

Technical Problem

The corrosion rate of existing biodegradable magnesium alloys in bone healing treatment devices is too fast, resulting in an increase in the pH of body fluids at the implanted site and interfering with bone healing. Although zinc alloys have certain antibacterial properties, their antibacterial strength is not enough to meet surgical needs.

Method used

Long-term high-efficiency antibacterial fully degraded medical zinc alloy/polylactic acid composite materials are prepared by using 3D printing technology. The zinc alloy wire is surface modified and melt blended with MXene and polylactic acid and extruded into wires to form a wire-slide composite sheet layer and then heat-pressed.

Benefits of technology

The long-term and efficient antibacterial function of the composite material is realized, the distribution state of zinc alloy wires in the composite material is regulated, the release of zinc ions is reduced, the cytotoxic effect is avoided, and the mechanical properties of the material are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116531575B_ABST
    Figure CN116531575B_ABST
Patent Text Reader

Abstract

The present invention discloses a long-lasting, highly effective, antibacterial and fully degradable medical zinc alloy / polylactic acid composite material and a preparation method thereof, which belongs to the field of medical materials. The preparation method comprises the following steps: step one, surface modification of zinc alloy wire; step two, melt blending and extruding polylactic acid and MXene containing characteristic functional groups to obtain modified polylactic acid wire; step three, directional arrangement of the zinc alloy wire after surface modification, and printing the modified polylactic acid wire layer by layer to obtain a wire-clamped composite sheet; step four, stacking and arranging a number of wire-clamped composite sheets or stacking and arranging a number of wire-clamped composite sheets and polylactic acid sheets alternately, and then hot pressing and forming. The present invention improves the interface bonding effect by changing the surface microstructure of the zinc wire, thereby achieving effective regulation of the mechanical attenuation and degradation performance of the composite material, and the Zn released by degradation 2+ It has the function of promoting bone formation, and the loaded MXene has the characteristics of long-term and high-efficiency antibacterial. The preparation method is highly efficient, low in energy consumption, and environmentally friendly and pollution-free.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of medical materials, and relates to an orthopedic internal fixation material, and in particular to a long-term, high-efficiency, antibacterial and fully degradable medical zinc alloy / polylactic acid composite material and a preparation method thereof. Background Art

[0002] In recent years, biodegradable metals represented by magnesium, zinc, iron and related alloys have become a research hotspot in the field of biomedical metal materials. Among them, the elastic modulus (40-45GPa) and density (1.7-2.0g / cm 3 ) is closer to human bones. Magnesium and magnesium alloys have been widely studied in bone healing therapeutic devices. However, the biggest problem with biodegradable magnesium alloys is that the corrosion rate is too fast. The alkaline products produced by degradation can easily lead to an increase in the pH value of the body fluid at the implant site, which to some extent interferes with the normal healing process of the bone and causes damage to the healing tissue.

[0003] As one of the essential trace elements in the human body, zinc plays an important role in promoting human growth and development, synthesizing a variety of essential enzymes in the human body, enhancing human immunity, and maintaining normal human appetite. The standard electrode potential of zinc (-0.763V) is between Mg (-2.372V) and Fe (-0.447V), and the degradation rate is also between the two. It can avoid the adverse effects of Mg degradation products on surrounding tissues due to excessive alkalinity or large amounts of hydrogen production, and can also avoid the same defects of iron as permanent implant materials due to slow degradation. Studies have shown that zinc and its alloys can promote human tissue repair after implantation in the human body, without obvious chronic inflammatory reactions, necrosis or hyperplasia. It is reported that the degradation rate of zinc wire (diameter 0.25mm, purity>99.99%) in the abdominal aorta of mice within 20 months is only 0.02mm / y and no toxicity is shown. Zinc alloy was used for internal fixation of mandibular fractures in dogs. The degradation rate of zinc alloy in the body was only 0.095±0.009mm / y after 24 weeks, showing good fracture fixation effect and the function of promoting the formation of new bone tissue. The good biodegradability and adaptability of zinc and its alloys to tissue regeneration make them have great application potential in orthopedics and cardiovascular departments.

[0004] However, human cells have limited tolerance to zinc ions. How to regulate the release rate of zinc ions so that it is within a safe range that the human body can tolerate has become a problem that needs to be solved. In addition, in the treatment of open fractures, the most common type of orthopedic trauma, effective infection control is the key to success. Although zinc has certain antibacterial properties, its antibacterial strength is only one thousandth of that of silver ions, which cannot achieve the desired antibacterial effect in surgery. Therefore, it is necessary to find materials with better antibacterial effects. Summary of the invention

[0005] The invention provides a long-term, high-efficiency, antibacterial and fully degradable medical zinc alloy / polylactic acid composite material and a preparation method thereof, so as to overcome the defects of the prior art.

[0006] To achieve the above object, the present invention provides a method for preparing a long-term, high-efficiency, antibacterial and fully degradable medical zinc alloy / polylactic acid composite material, which has the following characteristics:

[0007] Step 1: performing surface modification treatment on the zinc alloy wire to increase the surface roughness of the zinc alloy wire or forming a film layer containing functional groups that can chemically react with polylactic acid on the surface of the zinc alloy wire;

[0008] Step 2: melt-blending and extruding polylactic acid and MXene containing characteristic functional groups to obtain modified polylactic acid filaments for 3D printing, wherein the characteristic functional groups contained in MXene are functional groups that can improve compatibility with polylactic acid;

[0009] Step 3: align and fix the surface-modified zinc alloy wire obtained in step 1 on the loading platform of the 3D printer, and use the 3D printer to print the modified polylactic acid wire obtained in step 2 layer by layer on the oriented zinc alloy wire to obtain a wire-clamped composite sheet;

[0010] Step 4. Stack and arrange several wire-interlaced composite sheets obtained in step 3, or alternately stack and arrange several wire-interlaced composite sheets obtained in step 3 and polylactic acid sheets directly 3D-printed from modified polylactic acid filaments (adjust the distribution state of zinc alloy wire in the composite material by adjusting the distance between the wire-interlaced composite sheets), and then perform hot pressing to obtain a long-lasting, highly effective, antibacterial and fully degradable medical zinc alloy / polylactic acid composite material.

[0011] Furthermore, the present invention provides a method for preparing a long-term, high-efficiency, antibacterial and fully degradable medical zinc alloy / polylactic acid composite material, which may also have the following characteristics: wherein, in the long-term, high-efficiency, antibacterial and fully degradable medical zinc alloy / polylactic acid composite material, the volume fraction of zinc alloy wire is 5-40%, the mass fraction of MXene is 0.05-5%, and the mass fraction of polylactic acid is 60-95%.

[0012] Furthermore, the present invention provides a method for preparing a long-term, high-efficiency, antibacterial and fully degradable medical zinc alloy / polylactic acid composite material, which may also have the following characteristics: wherein the component of the zinc alloy wire is selected from at least one of Zn-Cu, Zn-Cu-Mg, Zn-Cu-Ca, Zn-Ag, and Zn-Mg, preferably Zn-0.2Cu-0.1Mg alloy (Zn 99.7wt.%, Cu 0.2wt.%, Mg 0.1wt.%).

[0013] Furthermore, the present invention provides a method for preparing a long-term, high-efficiency, antibacterial and fully degradable medical zinc alloy / polylactic acid composite material, which may also have the following characteristics: wherein the diameter of the zinc alloy wire is 0.2-0.5 mm, preferably 0.3 mm. The zinc alloy wire is prepared by smelting, extrusion, drawing, annealing, cleaning and other processes.

[0014] Furthermore, the present invention provides a method for preparing a long-term, highly effective, antibacterial and fully degradable medical zinc alloy / polylactic acid composite material, which may also have the following characteristics: wherein, in step one, the zinc alloy wire is surface modified by micro-arc oxidation, phosphating or silane coupling agent.

[0015] The phosphating method is to immerse the zinc alloy wire in a phosphating solution and perform phosphating treatment for 30-60 minutes at 20-30°C; the phosphating solution is a mixed solution of potassium dihydrogen phosphate and zinc phosphate, the concentration of potassium dihydrogen phosphate is 5-10g / L, and the concentration of zinc phosphate is 20-30g / L; the ratio of zinc alloy wire to phosphating solution is 10-30cm 2 / mL.

[0016] In the micro-arc oxidation treatment, the formula of the micro-arc oxidation electrolyte is Na2SiO3 10-20g / L, Na3PO4 1-10g / L, NaOH 1-5g / L, NaF 1-10g / L.

[0017] The method of surface modification treatment (silanization treatment) of silane coupling agent is: immerse the zinc alloy wire in 1-5mol / L alkaline solution for 1-5h, and the ratio of zinc alloy wire to alkaline solution is 10-30cm 2 / mL; at the same time, dilute KH560 with anhydrous ethanol to prepare a 5-15wt.% alcohol solution of silane coupling agent, and mechanically stir at 50-70°C for 1-3h to ensure that the siloxane groups are completely hydrolyzed. After that, immerse the zinc alloy wire pretreated with alkaline solution in the hydrolyzed KH560 solution at room temperature for 0.5-1h, take it out and age it in an oven at 100-150°C for 1-2h.

[0018] Furthermore, the present invention provides a method for preparing a long-term, highly effective, antibacterial and fully degradable medical zinc alloy / polylactic acid composite material, which may also have the following characteristics: wherein, in step 2, the characteristic functional groups contained in the MXene are one or more of hydroxyl, carboxyl and amine groups.

[0019] Furthermore, the present invention provides a method for preparing a long-term, high-efficiency, antibacterial and fully degradable medical zinc alloy / polylactic acid composite material, which may also have the following characteristics: wherein the MXene is selected from Ti3C2T x 、Ti2CT x 、Nb2CT x 、Mo2CTx 、Ti4N3T x 、Ta4C3T x 、V2CT x 、Zr3C2T x 、(Nb 0.8 Zr 0.2 )4C3T x One or more of the following, preferably Ti3C2T x .

[0020] Furthermore, the present invention provides a method for preparing a long-term, high-efficiency, antibacterial and fully degradable medical zinc alloy / polylactic acid composite material, which may also have the following characteristics: wherein, in step three, a twin-screw extruder is used to melt-blend and extrude polylactic acid and MXene containing characteristic functional groups, the processing temperature of the twin-screw extruder is 170-190°C, the rotation speed is 60-120r / min, and the diameter of the extruder die is 3mm or 1.75mm.

[0021] Furthermore, the present invention provides a method for preparing a long-term, high-efficiency, antibacterial and fully degradable medical zinc alloy / polylactic acid composite material, which may also have the following characteristics: wherein, in step four, the hot pressing temperature of the hot pressing molding is 160-185°C, the hot pressing pressure is 1-5MPa, the hot pressing time is 2-20min, the holding time is 30-60min, and the temperature is lowered to below 80°C to open the mold and take out the sample.

[0022] The present invention also provides a long-term, high-efficiency, antibacterial and fully degradable medical zinc alloy / polylactic acid composite material prepared by the above preparation method. The long-term, high-efficiency, antibacterial and fully degradable medical zinc alloy / polylactic acid composite material is mainly used for orthopedic internal fixation implants.

[0023] The beneficial effects of the present invention are:

[0024] 1. Since MXene has a large specific surface area, it can fully contact with bacteria, and the functional groups (-OH, -COOH) it carries can form hydrogen bonds with bacterial cell membrane lipopolysaccharides to inactivate bacteria. In addition to its high antibacterial effect, MXene can also improve the mechanical properties of composite materials. Therefore, introducing MXene components into the polylactic acid matrix can strengthen the matrix and give the composite material a long-term and high-efficiency antibacterial function.

[0025] Second, zinc alloy wire with a diameter of 0.2-0.5mm is used to directionally reinforce polylactic acid, and the interface bonding effect between Zn and PLA is changed by changing the surface microstructure of the zinc alloy wire. Specifically, after the surface of the zinc alloy wire is treated with micro-arc oxidation and phosphating, the surface roughness can be increased. In particular, after micro-arc oxidation, a rough and porous ceramic layer is formed on the surface of the zinc alloy wire. In the subsequent hot pressing process, the molten polylactic acid can easily penetrate into these holes. After the sample is cooled, a mechanically locked structure is formed between the two, which effectively improves the interface bonding effect; after treatment with a silane coupling agent, an organic film layer can be formed on the surface of the zinc alloy wire. The Si-OH contained in it can react chemically with the hydroxyl or carboxyl group at the end of the polylactic acid molecular chain. The two are combined together by chemical bonds, which can also effectively improve the interface bonding effect. That is, the directional and dispersed arrangement of the zinc alloy filaments in the polylactic acid matrix can play a role in directionally reinforcing the polylactic acid.

[0026] At the same time, the surface film structure generated after the surface treatment of zinc alloy wire can reduce the Zn 2+ The release of Zn 2+ The cytotoxic effect caused by excessive concentration. The alkalinity of the degradation products of Zn alloy and the acidity of the degradation products of polylactic acid are used to control the degradation rate of the composite material and the pH value of the degradation products, thereby reducing the inflammatory response caused by large changes in pH value in the implanted area.

[0027] 3. The present invention adopts 3D printing technology to prepare composite materials. By adjusting the process parameters, the cross-sectional shape of the wire-insulated composite sheet, the position and arrangement of the Zn alloy wire and the overall size of the composite material can be controlled. This preparation method has the advantages of high preparation efficiency, low energy consumption, and environmental protection and no pollution.

[0028] Fourth, the present invention disperses and composites the metal zinc alloy wire in the polymer matrix, which can avoid the use of organic solvents, and finally obtains the required composite material by hot pressing. No organic solvent is used in the preparation process, which can avoid the pollution caused by solvent consumption and the toxic effects caused by solvent residues in the final product, and achieve the purpose of energy saving, emission reduction, safety and environmental protection.

[0029] 5. The long-term, high-efficiency, antibacterial and fully degradable medical zinc alloy / polylactic acid composite material of the present invention is used in the field of orthopedic internal fixation materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 are the surface microscopic morphologies of the zinc alloy wires after different surface modification treatments in Examples 1-3, wherein a is the surface of the zinc alloy wire after micro-arc oxidation surface modification treatment in Example 2, b is the surface of the zinc alloy wire after phosphating surface modification treatment in Example 1, and c is the surface of the zinc alloy wire after silane coupling agent surface modification treatment in Example 3;

[0031] Figure 2 This is the morphology of the polylactic acid sheet layer with 0.05% MXene added in Example 1;

[0032] Figure 3 The macroscopic morphology of the long-term, high-efficiency, antibacterial and fully degradable medical zinc alloy / polylactic acid composite material (right) and the material without MXene added (left) prepared in Example 1;

[0033] Figure 4 Schematic diagram of wire distribution in the cross section of composite materials containing different volume fractions of zinc alloy wire. DETAILED DESCRIPTION

[0034] The present invention is further described below in conjunction with specific embodiments.

[0035] Example 1

[0036] This embodiment provides a long-term, high-efficiency, antibacterial and fully degradable medical zinc alloy / polylactic acid composite material, and a preparation method thereof comprises the following steps:

[0037] Step 1: Place the cleaned Zn alloy wire in 20cm increments. 2 / mL ratio was immersed in phosphating solution and phosphating was performed at 25°C for 40 minutes, wherein the composition of the phosphating solution was 8g / L potassium dihydrogen phosphate and 24g / L zinc phosphate. After the phosphating treatment, the Zn alloy wire was taken out, rinsed with deionized water until the pH value was neutral, dried and set aside. Figure 1 As shown in b.

[0038] Among them, the preparation method of Zn alloy wire is: a Zn-0.2Cu-0.1Mg alloy wire with a diameter of 0.3mm (composition is Zn 99.7wt.%, Cu 0.2wt.%, Mg 0.1wt.%) is made by melting, hot extrusion, cold drawing-heat treatment process. The smelting of Zn alloy is carried out in a pit-type resistance furnace with a graphite crucible. Before smelting, the clean and dry crucible is placed in the furnace and heated to 250°C with the furnace, and kept warm for 1h to remove moisture. The weighed pure zinc block is added to the graphite crucible, gradually heated to 650°C and kept warm for 30min under the protection of Ar gas and SF6 atmosphere, and the melt is stirred to ensure its uniform melting. Add weighed pure copper particles, stir evenly and keep warm for 30min. Then further add weighed pure magnesium particles, stir evenly and keep warm for 30min. Remove the impurities floating on the surface of the molten metal, turn off the heating system, and then cast the molten metal into a steel mold that has been preheated to 150°C. Cool the mold to near room temperature and take it out. Extrude the cast zinc alloy into a rod with a diameter of 10 mm. Through a cold drawing-heat treatment cycle, it is gradually drawn into a Zn alloy wire with a diameter of 0.3 mm. The prepared Zn alloy wire is ultrasonically cleaned with acetone, rinsed with deionized water, dried, and collected for use.

[0039] Step 2: Mix the PLA raw material and Ti3C2-COOH-MXene in a high mixer, wherein the mass fraction of Ti3C2-COOH-MXene is 0.05%, and then add them into a twin-screw extruder for melt blending and extrusion into filaments to obtain modified polylactic acid filaments for 3D printing. The processing temperature of each extrusion zone of the twin-screw extruder is set to 170-190°C, the speed is 60r / min, and the die diameter of the extruder is 1.75mm.

[0040] Step 3: Directly arrange and fix the phosphating Zn alloy wire on the loading platform of the 3D printer, and use the 3D printer to print the modified polylactic acid wire layer by layer to prepare the wire-clamped composite sheet. The printing process is as follows: Use Mimics software to design and draw the material model to be printed, load the modified polylactic acid wire into the barrel of the 3D printer, set the printing path and printing rate according to the model slice and wire feeding rate imported by the software, and obtain wire-clamped composite sheets with 6, 8, 10, 8 and 6 Zn alloy wires arranged respectively after printing. The width of the composite sheet is 4-6mm and the thickness is 0.5-1.0mm.

[0041] Step 4: Composite sheets containing 6, 8, 10, 8 and 6 Zn alloy wires are mixed with PLA sheets with 0.05% MXene added (made by 3D printing of the modified polylactic acid wire obtained in step 2, such as Figure 2 The long-term, high-efficiency, antibacterial and fully degradable medical zinc alloy / polylactic acid composite material with a volume fraction of 10% of Zn alloy wire is obtained by hot pressing. The macroscopic morphology is shown in FIG. Figure 3 As shown on the right side of the figure (the left side is the material without MXene added). The hot pressing temperature is 168°C, the hot pressing pressure is 1.0MPa, and the hot pressing is carried out for 3 minutes and then the pressure is maintained for 30 minutes. The temperature is lowered to below 80°C and the mold is opened to take out the sample. The cross-sectional wire distribution diagram of the sample is shown in the figure below. Figure 4 As shown, the number of Zn alloy wires in each layer can be controlled according to the amount of wire used (volume fraction vol%).

[0042] Example 2

[0043] This embodiment provides a long-term, high-efficiency, antibacterial and fully degradable medical zinc alloy / polylactic acid composite material, and a preparation method thereof comprises the following steps:

[0044] Step 1: Perform micro-arc oxidation on the cleaned Zn alloy wire. The formula of the micro-arc oxidation electrolyte is Na2SiO3 13g / L, Na3PO4 5g / L, NaOH 2.5g / L, NaF 6g / L. After the micro-arc oxidation treatment, take out the Zn alloy wire, rinse it with deionized water until the pH value is neutral, dry it, and collect it for later use. Figure 1 As shown in a.

[0045] Wherein, the preparation method of Zn alloy wire is the same as that in Example 1.

[0046] Step 2: Mix the PLA raw material and Ti3C2-OH MXene in a high mixer, wherein the mass fraction of Ti3C2-OH MXene is 0.1%, add them into a twin-screw extruder for melt blending and extrusion into filaments to obtain modified polylactic acid filaments for 3D printing. The processing temperature of each extrusion zone of the twin-screw extruder is set to 170-190°C, the speed is 80r / min, and the die diameter of the extruder is 1.75mm.

[0047] Step 3: Directly arrange and fix the Zn alloy wire after micro-arc oxidation on the loading platform of the 3D printer, and use the 3D printer to print the modified polylactic acid wire layer by layer to prepare the wire-clamped composite sheet. The printing process is as follows: Use Mimics software to design and draw the material model to be printed, load the modified polylactic acid wire into the barrel of the 3D printer, set the printing path and printing rate according to the model slice and wire feeding rate imported by the software, and obtain wire-clamped composite sheets with 3, 4, 5, 4 and 3 Zn alloy wires arranged after printing. The width of the composite sheet is 4-6mm and the thickness is 0.5-1.0mm.

[0048] Step 4. Alternately stack the wire-inserted composite sheets containing 3, 4, 5, 4 and 3 Zn alloy wires and the PLA sheets with 0.1% MXene added, and hot press to obtain a long-lasting, highly effective, antibacterial and fully degradable medical zinc alloy / polylactic acid composite material with a volume fraction of 5% Zn alloy wire. The hot pressing temperature is 162°C, the hot pressing pressure is 1.0MPa, and the pressure is maintained for 30 minutes after hot pressing for 2 minutes. The temperature is lowered to below 80°C, the mold is opened, and the sample is taken out. The schematic diagram of the cross-sectional wire distribution of the sample is shown in the figure. Figure 4 shown.

[0049] Example 3

[0050] This embodiment provides a long-term, high-efficiency, antibacterial and fully degradable medical zinc alloy / polylactic acid composite material, and a preparation method thereof comprises the following steps:

[0051] Step 1: Place the cleaned Zn alloy wire at room temperature at 20 cm 2 / mL ratio was immersed in a sodium hydroxide solution (3 mol / L) for 3 h. At the same time, KH560 was diluted with anhydrous ethanol to prepare a 10 wt.% alcohol solution of silane coupling agent, which was mechanically stirred at 60 °C for 2 h to ensure that the siloxane groups were completely hydrolyzed. Afterwards, the Zn alloy wire pretreated with the alkaline solution was immersed in the hydrolyzed KH560 solution at room temperature for 0.5 h, taken out and aged in an oven at 120 °C for 1 h. After the silanization treatment, the Zn alloy wire was taken out, rinsed with deionized water until the pH value was neutral, dried in a vacuum drying oven at 70 °C, collected and set aside. The treated Zn alloy wire was as follows Figure 1 As shown in c.

[0052] Among them, the preparation method of Zn alloy wire is the same as that in Example 1.

[0053] Step 2: Mix the PLA raw material and Ti3C2-OH MXene in a high mixer, wherein the mass fraction of Ti3C2-OH MXene is 0.1%, add them into a twin-screw extruder for melt blending and extrusion into filaments to obtain modified polylactic acid filaments for 3D printing. The processing temperature of each extrusion zone of the twin-screw extruder is set to 170-190°C, the speed is 90r / min, and the die diameter of the extruder is 1.75mm.

[0054] Step 3: Directly arrange and fix the silanized Zn alloy wire on the loading platform of the 3D printer, and use the 3D printer to print the modified polylactic acid wire layer by layer to prepare the wire-clamped composite sheet. The printing process is as follows: Use Mimics software to design and draw the material model to be printed, load the modified polylactic acid wire into the barrel of the 3D printer, set the printing path and printing rate according to the model slice and wire feeding rate imported by the software, and after printing, obtain wire-clamped composite sheets with 5, 6, 7, 8, 10, 8, 7 and 6 Zn alloy wires arranged respectively. The width of the composite sheet is 4-6mm and the thickness is 0.5-1.0mm.

[0055] Step 4. Alternately stack the wire-inserted composite sheets containing 5, 6, 7, 8, 10, 8, 7 and 6 Zn alloy wires and the PLA sheets with 0.1% MXene added, and hot press to obtain a long-lasting, highly effective, antibacterial and fully degradable medical zinc alloy / polylactic acid composite material with a Zn alloy wire volume fraction of 15%. The hot pressing temperature is 170°C, the hot pressing pressure is 1.0MPa, and the pressure is maintained for 30 minutes after hot pressing for 3 minutes. The temperature is lowered to below 80°C, the mold is opened, and the sample is taken out. The schematic diagram of the cross-sectional wire distribution of the sample is shown in the figure. Figure 4 shown.

[0056] Example 4

[0057] This embodiment provides a long-term, high-efficiency, antibacterial and fully degradable medical zinc alloy / polylactic acid composite material, and a preparation method thereof comprises the following steps:

[0058] Step 1: The Zn alloy wire is subjected to micro-arc oxidation surface modification treatment, phosphating surface modification treatment and silane coupling agent surface modification treatment respectively, and the treatment methods are the same as those in Example 1, Example 2 and Example 3. The preparation method of the Zn alloy wire is the same as that in Example 1.

[0059] Step 2: Mix the PLA raw material and Ti3C2-COOH-MXene in a high mixer, wherein the mass fraction of Ti3C2-OH-MXene is 0.0.5%, add them into a twin-screw extruder for melt blending and extrusion into filaments to obtain modified polylactic acid filaments for 3D printing. The processing temperature of each extrusion zone of the twin-screw extruder is set to 170-190°C, the speed is 80r / min, and the die diameter of the extruder is 1.75mm.

[0060] Step 3: Directly arrange and fix the Zn alloy wires after micro-arc oxidation, phosphating and silanization on the loading platform of the 3D printer, and use the 3D printer to print the modified polylactic acid wire layer by layer to prepare the wire-clamped composite sheet. The printing process is as follows: Use Mimics software to design and draw the material model to be printed, load the modified polylactic acid wire into the barrel of the 3D printer, set the printing path and printing rate according to the model slice and wire feeding rate imported by the software, and after printing, obtain the wire-clamped composite sheet with 6 silanized Zn alloy wires, 8 micro-arc oxidized Zn alloy wires and 10 phosphating Zn alloy wires. The width of the composite sheet is 4-6mm and the thickness is 0.5-1.0mm.

[0061] Step 4: symmetrically stack and arrange the wire-inserted composite sheet containing 6 silanized Zn alloy wires, 8 micro-arc oxidized Zn alloy wires, and 10 phosphated Zn alloy wires layer by layer with the PLA sheet added with 0.05% MXene, and then hot press to obtain a long-term, high-efficiency, antibacterial and fully degradable medical zinc alloy / polylactic acid composite material with an outer layer of silanized Zn alloy wire, a middle layer of micro-arc oxidized Zn alloy wire, and an inner layer of phosphated Zn alloy wire, wherein the total volume fraction of Zn alloy wire is 10%. The hot pressing temperature is 168°C, the hot pressing pressure is 1.0MPa, the hot pressing is 3 minutes, the pressure is maintained for 30 minutes, the temperature is lowered to below 80°C, the mold is opened, and the sample is taken out.

[0062] The antibacterial performance evaluation experiment of long-term high-efficiency antibacterial and fully degradable medical zinc alloy / polylactic acid composite material was carried out:

[0063] ATCC25922 Escherichia coli strain was selected to qualitatively evaluate the antibacterial effect of the composite material. The strain was added to 30 mL of Luria-Bertani (LB) nutrient solution and incubated at 37 ° C for 16 h. After that, the suspension was removed by centrifugation and the precipitate was washed 3 times with PBS buffer solution. Finally, the treated bacteria were resuspended in 1 mL of PBS buffer solution for use. The glassware and solutions used in the experiment were sterilized in a 121 ° C autoclave for 20 min in advance and set aside. PLA, Zn wire / PLA composite materials and Zn wire / PLA composite materials with MXene added (long-term, high-efficiency, antibacterial and fully degradable medical zinc alloy / polylactic acid composite materials) were sterilized by ethylene oxide and placed in different culture dishes, and 20 mL of sterile milk was added to each culture dish. The culture dishes were cultured in a constant temperature incubator at 37 ° C for 24 h. After that, the state of the milk was observed. The composition of the substances added to each group of culture dishes is as follows:

[0064] Group 1: 20 mL milk;

[0065] Group 2: PLA+20mL milk+100μL bacterial solution;

[0066] Group 3: Zn silk / PLA composite material + 20 mL milk + 100 μL bacterial solution;

[0067] Group 4: Zn silk / PLA composite material with MXene added + 20 mL milk + 100 μL bacterial solution;

[0068] Group 5: Zn silk / PLA composites after immersion in sterilized Hank's solution for 60 days + 20 mL milk + 100 μL bacterial solution;

[0069] Group 6: Zn silk / PLA composites containing MXene after immersion in sterilized Hank's solution for 60 days + 20 mL milk + 100 μL bacterial solution;

[0070] The results show that a small number of colonies appeared in the culture dishes of Groups 1 and 2, indicating that milk itself and PLA have no antibacterial function. There were basically no colonies in the culture dishes of Group 3, indicating that this group of composite materials has good antibacterial function. There were no colonies in the culture dishes of Group 4, indicating that this group of composite materials has good antibacterial function. There were no colonies in the culture dishes of Groups 5 and 6, indicating that this group of composite materials has good long-term and high-efficiency antibacterial function.

[0071] The preparation method of the present invention is easy to accurately control the overall size of the composite material, the distribution and amount of the zinc alloy wire, and can effectively control the mechanical attenuation and degradation performance of the composite material by changing the surface microstructure of the zinc wire to improve the interface bonding effect. 2+ It has the function of promoting bone formation and is expected to be used in the field of orthopedic internal fixation materials. The loaded MXene has the characteristics of long-term and high-efficiency antibacterial, which can effectively reduce the risk of bacterial infection in the implant area. The present invention combines zinc with a degradable polymer material to prepare a composite material. During the degradation process, the alkaline product produced by the degradation of zinc is used to accelerate the degradation of PLA. In the later stage of degradation, the acidic product produced by the degradation of PLA promotes the degradation of zinc. The degradation rate of the composite material is regulated by the interaction between the components. The zinc lactate produced by the degradation can be regarded as Zn 2+ The sustained-release carrier can relieve the 2+ It can eliminate the cytotoxic effects caused by excessive concentrations while also acting as a zinc supplement.

[0072] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0073] The above are only preferred embodiments of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, some improvements and modifications without departing from the principle of the present invention should be regarded as the protection scope of the present invention.

Claims

1. A method for preparing an antibacterial and fully degradable medical zinc alloy / polylactic acid composite material, characterized in that: The following steps are involved: Step 1: performing surface modification treatment on the zinc alloy wire to increase the surface roughness of the zinc alloy wire or forming a film layer containing functional groups capable of chemically reacting with polylactic acid on the surface of the zinc alloy wire; Step 2: melt-blending and extruding polylactic acid and MXene containing characteristic functional groups to obtain modified polylactic acid filaments for 3D printing, wherein the characteristic functional groups contained in MXene are functional groups that can improve compatibility with polylactic acid; The MXene is selected from Ti3C2T x 、Ti2CT x 、Nb2CT x 、Mo2CT x 、Ti4N3T x 、Ta4C3T x 、V2CT x 、Zr3C2T x 、(Nb 0.8 Zr 0.2 )4C3T x One or more of the following; Step 3: align and fix the surface-modified zinc alloy wire obtained in step 1 on the loading platform of the 3D printer, and use the 3D printer to print the modified polylactic acid wire obtained in step 2 layer by layer on the oriented zinc alloy wire to obtain a wire-clamped composite sheet; Step 4: stack and arrange several wire-clamped composite sheets obtained in step 3, or alternately stack and arrange several wire-clamped composite sheets obtained in step 3 and polylactic acid sheets 3D-printed from modified polylactic acid filaments, and then perform hot pressing to obtain an antibacterial and fully degradable medical zinc alloy / polylactic acid composite material.

2. The method for preparing the antibacterial and fully degradable medical zinc alloy / polylactic acid composite material according to claim 1, characterized in that: in, In the antibacterial and fully degradable medical zinc alloy / polylactic acid composite material, the volume fraction of zinc alloy wire is 5-40%, the mass fraction of MXene is 0.05-5%, and the mass fraction of polylactic acid is 60-95%.

3. The method for preparing the antibacterial and fully degradable medical zinc alloy / polylactic acid composite material according to claim 1, characterized in that: in, The component of the zinc alloy wire is selected from at least one of Zn-Cu, Zn-Cu-Mg, Zn-Cu-Ca, Zn-Ag, and Zn-Mg.

4. The method for preparing the antibacterial and fully degradable medical zinc alloy / polylactic acid composite material according to claim 1, characterized in that: in, The diameter of the zinc alloy wire is 0.2-0.5 mm.

5. The method for preparing the antibacterial and fully degradable medical zinc alloy / polylactic acid composite material according to claim 1, characterized in that: in, In step one, the zinc alloy wire is subjected to surface modification treatment by micro-arc oxidation, phosphating or silane coupling agent.

6. The method for preparing the antibacterial and fully degradable medical zinc alloy / polylactic acid composite material according to claim 1, characterized in that: in, In step 2, the characteristic functional groups contained in the MXene are hydroxyl, carboxyl or amine.

7. The method for preparing the antibacterial and fully degradable medical zinc alloy / polylactic acid composite material according to claim 1, characterized in that: in, In step 2, a twin-screw extruder is used to melt-blend and extrude polylactic acid and MXene containing characteristic functional groups. The processing temperature of the twin-screw extruder is 170-190° C., the rotation speed is 60-120 r / min, and the diameter of the extruder die is 3 mm or 1.75 mm.

8. The method for preparing the antibacterial and fully degradable medical zinc alloy / polylactic acid composite material according to claim 1, characterized in that: in, In step 4, the hot pressing temperature of the hot pressing molding is 160-185°C, the hot pressing pressure is 1-5MPa, the hot pressing time is 2-20min, the holding time is 30-60min, the temperature is lowered to below 80°C, the mold is opened and the sample is taken out.

9. An antibacterial and fully degradable medical zinc alloy / polylactic acid composite material obtained by the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Preparation method for MXene reinforced polylactic-acid 3D printing material and product

    CN109608841A

  • Preparation method and applications of antibacterial and biodegradable zinc alloy anastomosis nail

    CN111012420A